2009
DOI: 10.1016/j.expneurol.2009.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Circadian activity associated with spatial learning and memory in aging rhesus monkeys

Abstract: In rodents, spatial learning and memory tests require navigation, whereas in nonhuman primates these tests generally do not involve a navigational component, thus assessing nonhomologous neural systems. To allow closer parallels between rodent and primate studies, we developed a navigational spatial learning and memory task for nonhuman primates and assessed the performance of elderly (19-25 years) female rhesus monkeys (Macaca mulatta). The animals were allowed to navigate in a room containing a series of foo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 54 publications
0
37
0
Order By: Relevance
“…An example of this self-sustained rhythmicity is illustrated in figure 1. The motor activity data depicted in figure 1a were obtained from an adult rhesus macaque using an Actiwatch, and emphasize the highly entrained diurnal pattern of activity that occurs under fixed 12L:12D photoperiods [33,34,35,36]. In addition, the data show how the activity rhythm becomes free-running, with slight phase advancement, when the animal is exposed to continuous dim illumination (30 lx).…”
Section: Circadian Hormone Rhythms Help With Adaptation To Daily Envimentioning
confidence: 86%
“…An example of this self-sustained rhythmicity is illustrated in figure 1. The motor activity data depicted in figure 1a were obtained from an adult rhesus macaque using an Actiwatch, and emphasize the highly entrained diurnal pattern of activity that occurs under fixed 12L:12D photoperiods [33,34,35,36]. In addition, the data show how the activity rhythm becomes free-running, with slight phase advancement, when the animal is exposed to continuous dim illumination (30 lx).…”
Section: Circadian Hormone Rhythms Help With Adaptation To Daily Envimentioning
confidence: 86%
“…Prolonged circadian desynchronization can lead to increased mortality in aged animals (Davidson et al 2006). Age-associated alterations in circadian rhythms also impact memory and performance in animal models (Haley et al 2009;Kondratova et al 2010;Nakamura et al 2011), while in older individuals, fragmentation of rest-activity cycles is correlated with cognitive decline in mental speed, memory, and executive function (Oosterman et al 2009). The interaction between circadian rhythms and cognitive function in aged individuals represents an area of escalating concern given the rising age of modern societies.…”
Section: The Circadian Clock Aging and Neurodegenerative Diseasesmentioning
confidence: 99%
“…In this test, the animals are placed in an open room containing food ports mounted to the wall. Nonhuman primates are trained to retrieve a food reward from a single baited port (33). Recently, we reported that during the first half of the trials, old female rhesus macaques mostly use a serial search pattern to find the baited port.…”
Section: Nonhuman Primatesmentioning
confidence: 99%